Sharia hotel development strategy - Jaidil Kamal; Andri Soemitra; Zuhrinal M. Nawawi (Jurnal Konseling dan Pendidikan, 2025)
This research aims to analyze the challenges, propose solutions, and formulate a development strategy model for sharia-compliant hotels in Riau Province. The study is motivated by the growing demand for sharia-based accommodations among Muslim tourists, alongside various challenges faced by sharia-compliant hotels, including issues related to legality, services, and infrastructure. The research employs the Analytic Network Process (ANP) method using Super Decisions software and involves nine expert informants, comprising academics, regulators, and hotel managers, selected through purposive sampling. The findings indicate that the challenges in developing sharia-compliant hotels in Riau Province can be classified into two main categories: internal challenges (e.g., management, human resources, and financial capacity), and external challenges (especially the roles of the National Sharia Council (NSC), the Indonesian Ulema Council (IUC), and government regulations). Consensus among respondents highlights those external challenges, particularly those related to the NSC and IUC, are the most critical, with an agreement level of 75%. Proposed solutions are also categorized as internal and external, with the top priority being solutions to external challenges, specifically those related to the NSC and IUC (96%). The development model identifies seven main strategies, with the highest priority being the establishment of a hotel entrepreneurs' forum (87%), followed by socialization and education programs. This research recommends strengthening the regulatory and educational roles of the NSC and IUC, as well as establishing an entrepreneurs' forum as a platform for synergy among stakeholders. The implementation of these two key strategies is expected to foster an integrated and sustainable ecosystem for the development of sharia-compliant hotels in Riau Province.